Development of liposomal vectors for effective delivery of pleiotropic recombinant leukemia inhibitory factor (LIF) cytokine - Pinho, Vanessa Tatiana (2020)
Dissertação de mestrado em Bioquímica Aplicada (área de especialização em Biomedicina)